Against ecological romanticism : Verrier Elwin and the making of an anti-modern tribal identity - Prasad, Archana (Three Essays Collective, 2011)
The essays in this book develop a systematic critique of the romanticised notions of tribal life, identity and ecology that informs so much of today’s scholarship as well as the popular perceptions and ‘everyday commonsense’ relating to these themes. The author has examined genesis of certain visions found in the work of Verrier Elwin, the grand old man of Indian anthropology and ‘tribal’ policy, and has shown how it links up with the contemporary realities of ethnicity, caste and community in India. The revised and updated version of this book also explores the gender dimension within tribal societies to strengthen its argument. The framework advanced in this book contests the hegemonic neo-liberal and hindutva visions of these decades of economic reforms.